Laporan Kasus : Henoch Schnolein Purpura dengan Keterlibatan Sendi dan Gastrointestinal - Nandya Dwizella; Umi Rinasari; Nevristia Pratama (Medula, 2023)
Henoch Schnolein Purpura (HSP) is one of the most Idiopatic Cutaneous Necrotizing Venulitis/Vasculitis, generally found on children compared to adult. The diagnosis HSP based on clinical manifestation which characterized purpuric with one or more following  athralgia/arteritis, renal involvement, gastrointestinal involvement or  Ig-A deposit  in tissue biopsy.  The aim is report a case of HSP with joint and gastrointestinal involvement. A 20-year-old woman came with red spots on both lower limbs and felt  joint pain and vomit, a history of similar red spot and joint pain felt intermittent since 6 years ago. There was history of pain in oral cavity 2 days before red spot appear.  Physical examination, vital signs were within normal limits, epigastric tenderness was found in abdominal examination. Dermatological examination in the cruris-dorsum pedis bilateral found macula erythematous, multiple, milier-lenticular, well-demarcated, discrete-confluent. Patients are diagnosed with HSP according to the clinical symptoms. Trigger factor for HSP is a history of infection. The patient was treated with acetaminophen, steroids, and topical therapy. Most HSP is self-limiting disease, supportive therapy is given to reduce clinical manifestation  and administration of corticosteroids prevent gastrointestinal complication